Deep Convolutional Neural Network-Based Detection of Bone Abnormalities in Musculoskeletal Radiographs - U. M., Prakash; N., Arivazhagan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Musculoskeletal abnormalities typically rely on radiographic examinations for diagnosis, but even experienced radiologists can miss abnormalities, underscoring the need for improved detection methods. This paper presents a novel approach utilizing Deep Convolutional Neural Networks (Deep CNN) for computer-aided bone abnormality detection. Leveraging the Stanford MURA dataset featuring radiological images of seven upper extremity types, we employ pre-processing techniques such as Histogram Equalization (HE) and Contrastive Limited Adaptive Histogram Equalization (CLAHE) to enhance image quality before inputting them into our proposed 5SET (5S) model. This model accurately classifies images into the seven upper extremity categories and identifies normal or abnormal conditions. Our results demonstrate a remarkable overall accuracy of 92.10%, with a precision of 94% for specific extremities and a Cohen’s Kappa score of 91.5%. This proposed model highlights the efficacy of combining preprocessing techniques with Deep CNN for high-precision bone abnormality detection.